2017
DOI: 10.1088/1742-6596/939/1/012019
|View full text |Cite
|
Sign up to set email alerts
|

First-principles simulation on thermoelectric properties in Bi-Sb System

Abstract: Abstract. Thermoelectric properties of bismuth-antimony (Bi-Sb) alloy system were simulated on the basis of first-principles calculation, to discuss the potential for thermoelectric devices. Atomistic model structures of Bi-Sb alloy system were devised in the forms of single-crystal bulk and one-dimensional nanowire under the periodic boundary condition. The cell parameters of the bulk model were simulated with respect to temperature by the quasiharmonic approximation through phonon calculation, and dependence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Different engineering approaches are implemented to improve the ZT value of various materials including V‐V binary crystals. First‐principles simulations have indicated that the composition of bulk Bi 1− x Sb x has no effect on the ZT value . Te doping can enhance the ZT value of bulk Bi 1− x Sb x by one order of magnitude .…”
Section: Applications Of 2d V‐v Binary Materialsmentioning
confidence: 99%
“…Different engineering approaches are implemented to improve the ZT value of various materials including V‐V binary crystals. First‐principles simulations have indicated that the composition of bulk Bi 1− x Sb x has no effect on the ZT value . Te doping can enhance the ZT value of bulk Bi 1− x Sb x by one order of magnitude .…”
Section: Applications Of 2d V‐v Binary Materialsmentioning
confidence: 99%